Selenoprotein P expression in glioblastoma as a regulator of ferroptosis sensitivity: preservation of GPX4 via the cycling-selenium storage - Zheng, Xi; Toyama, Takashi; Siu, Stephanie; Kaneko, Takayuki; Sugiura, Hikari; Yamashita, Shota; Shimoda, Yoshiteru; Kanamori, Masayuki; Arisawa, Kotoko; Endo, Hidenori; Saito, Yoshiro (Scientific reports, 2024)
Glioblastoma (GBM) is one of the most aggressive and deadly brain tumors; however, its current therapeutic strategies are limited. Selenoprotein P (SeP; SELENOP, encoded by the SELENOP gene) is a unique selenium-containing protein that exhibits high expression levels in astroglia. SeP is thought to be associated with ferroptosis sensitivity through the induction of glutathione peroxidase 4 (GPX4) via selenium supplementation. In this study, to elucidate the role of SeP in GBM, we analyzed its expression in GBM patients and found that SeP expression levels were significantly higher when compared to healthy subjects. Knock down of SeP in cultured GBM cells resulted in a decrease in GPX1 and GPX4 protein levels. Under the same conditions, cell death caused by RSL3, a ferroptosis inducer, was enhanced, however this enhancement was canceled by supplementation of selenite. These results indicate that SeP expression contributes to preserving GPX and selenium levels in an autocrine/paracrine manner, i.e., SeP regulates a dynamic cycling-selenium storage system in GBM. We also confirmed the role of SeP expression in ferroptosis sensitivity using patient-derived primary GBM cells. These findings indicate that expression of SeP in GBM can be a significant therapeutic target to overcome anticancer drug resistance.